2007
DOI: 10.1016/j.bbrc.2006.12.188
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of Akt phosphorylation and activity in response to EGF and insulin treatment

Abstract: The protein kinase Akt is a critical regulator of cell function and its overexpression and activation have been functionally linked to numerous pathologies such as cancer. Previous reports regarding the mechanism regulating Akt's activation have revealed two phosphorylation events, at threonine 308 (T308) and serine 473 (S473), as necessary for the full activation of the kinase in response to insulin. For this reason and because of the availability of phospho-specific antibodies to both T308 and S473, many stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 17 publications
0
25
1
Order By: Relevance
“…Furthermore, increased EGFR, but not InR, mediates these effects in the neurons, at least in affecting animal longevity. In fact, other works have also reported that downstream signaling that EGFR activates Akt is not exactly the same as InR actives Akt (Borisov et al., ; Kumar, Afeyan, Sheppard, Harms & Lauffenburger, ; Roudabush, Pierce, Maudsley, Khan & Luttrell, ). Although the molecular reason behind the differential functions of Akt in different cell types is unclear, the cell type‐specific molecular property of Akt may provide a means of differentially and precisely regulating the functions of various areas of the brain under different physiological conditions.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, increased EGFR, but not InR, mediates these effects in the neurons, at least in affecting animal longevity. In fact, other works have also reported that downstream signaling that EGFR activates Akt is not exactly the same as InR actives Akt (Borisov et al., ; Kumar, Afeyan, Sheppard, Harms & Lauffenburger, ; Roudabush, Pierce, Maudsley, Khan & Luttrell, ). Although the molecular reason behind the differential functions of Akt in different cell types is unclear, the cell type‐specific molecular property of Akt may provide a means of differentially and precisely regulating the functions of various areas of the brain under different physiological conditions.…”
Section: Discussionmentioning
confidence: 93%
“…2A). Our long-term, sustained, in vivo treatment displayed a well-established sign of activation of the phosphatidylinositol-3 kinase (PI3K)/Akt pathway (Kumar et al, 2007). Two-way ANOVA demonstrated an effect of the factor treatment for Akt Ser473 levels [F(1,22) = 12.2, P = 0.002].…”
Section: Proinsulin Induced the Akt Pathway In Samp8 Hippocampusmentioning
confidence: 98%
“…Its activation can be initiated by various extracellular signals that turn on PI3K (Engelman et al, 2006). After stimulus affecting on its respective receptor (Kumar et al, 2007), PI3K is activated and then phosphorylates inositol lipids (Bevan, 2001). This results in the production of PI3,4,5P3 and PI3,4P2 at the plasma membrane (Cantrell, 2001).…”
mentioning
confidence: 99%